TREM2/DAP12 Complex Regulates Inflammatory Responses in Microglia via the JNK Signaling Pathway - Zhong, Li; Zhang, Zhen-Lian; Li, Xinxiu; Liao, Chunyan; Mou, Pengfei; Wang, Tingting; Wang, Zongqi; Wang, Zhe; Wei, Min; Xu, Huaxi; Bu, Guojun; Chen, Xiao-Fen (Frontiers in Aging Neuroscience, 2017)
DNAX-activating protein of 12 kDa (DAP12) is a signaling adapter protein expressed in cells that participate in innate immune responses. By pairing with different triggering receptors expressed on myeloid cell (TREM) proteins, DAP12 can mediate both positive and negative cellular responses. In particular, TREM1 acts as an amplifier of the immune response, while TREM2 functions as a negative regulator. TREM2 has also been shown to stimulate the phagocytosis of apoptotic neurons and define the barrier function in microglia. Notably, loss-of-function mutations of either DAP12 or TREM2 result in a disorder known as Nasu-Hakola disease; and mutations of these genes have been associated with the risk for Alzheimer’s disease, suggesting that TREM2 and DAP12 may regulate common signaling pathways in the disease pathogenesis. In this study, we demonstrated an anti-inflammatory role of DAP12 in murine microglia that depends on the presence of TREM2. We also uncovered the JNK signaling pathway as the underlying molecular mechanism by which the TREM2/DAP12 complex suppresses the hyperactivation of microglia upon LPS stimulation. Interestingly, LPS down-regulates the expression of Trem2 via the activation of JNK and NF-κB signaling pathways, resulting in a vicious cycle that synergistically promotes the inflammatory responses. Our study provides insights into mechanism-based therapy for neuroinflammatory disorders.